Downregulation of PPARγ by miR-548d-5p suppresses the adipogenic differentiation of human bone marrow mesenchymal stem cells and enhances their osteogenic potential - Junkui Sun; Yisheng Wang; Yuebai Li; Guoqiang Zhao (2014)
Human bone marrow mesenchymal stem cells (hBMSCs) are multipotent cells that can differentiate into a variety of cell types. Elevated expression of peroxisome proliferator-activated receptor-γ (PPARγ) promotes the adipogenic differentiation of hBMSCs, and reduces their osteogenic differentiation. MicroRNAs (miRNAs) have been shown to play important roles in the regulation of hBMSCs differentiation. Because bioinformatic analysis has indicated that PPARγ is a candidate target of miR-548d-5p, the aim of this study was to assess the impact of miR-548d-5p on the dexamethasone-induced adipogenic differentiation of hBMSCs. A quantitative RT-PCR (qRT-PCR) assay was used to compare miR-548d-5p expression levels in dexamethasone-induced hBMSCs and uninduced control cells. Oil red O staining, cellular triglyceride (TG) content, and the mRNA and protein levels of PPARγ and CCAAT/enhancer binding protein α (C/EBPα) were used to evaluate the adipogenic differentiation of hBMSCs. Alkaline phosphatase (ALP) activity and levels of osteocalcin (OCN) and Runx2 were used to evaluate the osteogenic potential of hBMSCs. Compared with untreated cells, miR-548d-5p expression levels were downregulated during dexamethasone-induced adipogenic differentiation of hBMSCs. In contrast to the profuse Oil Red O staining in the cytoplasm of dexamethasone + scrambled miRNA-treated cells, there was limited staining in the cytoplasm of dexamethasone + miR-548d-5p-treated cells, indicating the absence of adipocytes. Moreover, compared with scrambled miRNA-treated cells, treatment with miR-548d-5p suppressed cellular levels of PPARγ and C/EBPα mRNA and protein, and cell TG content (P < 0.05). In contrast, compared with scrambled miRNA-treated cells, cellular levels of OCN and Runx2 mRNA and protein, as well as ALP activity, were significantly higher in miR-548d-5p-treated cells (P < 0.05). Western blot and luciferase reporter assays confirmed that miR-548d-5p directly targeted the 3′-untranslated region of PPARγ. miR-548d-5p is downregulated during dexamethasone-induced adipogenic differentiation of hBMSCs. By directly targeting and downregulating PPARγ, miR-548d-5p suppresses the dexamethasone-induced adipogenic differentiation of hBMSCs and enhances their osteogenic potential. Our findings suggest that miR-548d-5p has potential in the treatment of corticosteroid-induced osteonecrosis of the femoral head.